Researching children, intersectionality, and diversity in the digital age. Issue 1 (2nd January 2016) - Alper, Meryl; Katz, Vikki S.; Clark, Lynn Schofield
Abstract: Research on children's and adolescents' experiences with media and technology over the past century has largely echoed the concerns of the middle-class and majority culture. We discuss scholars' corrective efforts, particularly in recent years, in moving beyond these narrow foci to investigate how young people situated across social classes, racial and ethnic boundaries, and forms of disability engage with new media. In particular, we examine how scholars have conceptualized similarities and differences among children and families in relation to interconnected systems of oppression and privilege. We discuss how their work has challenged deficit-based approaches to cultural and social difference to understand how diverse families and young people actively negotiate media and technologies in everyday life. We argue that an intersectional, asset-oriented approach to studying the lived experiences of youth and families opens exciting new avenues for research that prioritizes the rights of children and adolescents in the digital age.